Efficacy and safety of upadacitinib in the treatment of moderate-to-severe atopic dermatitis: A systematic review. - Dan-Jie Zhao; Xia Li; Hai-Xia Lin; Hong Zheng; Di Zhou; Peng Tang (PLoS ONE)
Objective To evaluate the efficacy and safety of upadacitinib in the treatment of moderate-to-severe atopic dermatitis (AD), and provide reference for rational clinical medication. Methods PubMed, Medline, Embase, Web of Science, Clinical Trials Website, and Cochrane Library databases were searched from the time of establishment until January 6, 2024, to compile a list of all randomized controlled trials (RCTs) including upadacitinib in the treatment of moderate-to-severe AD. The quality of the included studies was evaluated using the Cochrane Systematic Review. Review Manager 5.3 software was utilized for statistical analysis of outcome measures. Results A total of five studies were included in the meta-analysis. The results revealed that the 15 mg and 30 mg upadacitinib significantly improved Eczema Area and Severity Index (EASI) 75% {[Odds Ratio (OR) = 8.58, 95% confidence interval (CI) (5.84-12.60), P < 0.00001] [OR = 15.62, 95% CI (10.89-22.42), P < 0.00001]}, Numerical Rating Scale (NRS) ≥ 4 {[OR = 7.13, 95% CI (5.63-9.01), P < 0.00001] [OR = 11.30, 95% CI (8.93-14.31), P < 0.00001]}, and Investigator's Global Assessment (IGA) 0/1 {[OR = 8.63, 95% CI (6.60-11.27), P < 0.00001] [OR = 16.04, 95% CI (12.26-20.99), P < 0.00001]} compared to placebo. In terms of safety, although 15 mg and 30 mg upadacitinib significantly increased the overall adverse events rate compared to placebo {[OR = 1.31, 95% CI (1.09-1.58), P = 0.004] [OR = 1.85, 95% CI (1.54-2.21), P < 0.00001]}, there was no significant difference in the serious adverse events rate {[OR = 0.73, 95% CI (0.41-1.29), P = 0.28] [OR = 0.69, 95% CI (0.39-1.23), P = 0.21]} and withdrawal rate due to adverse events {[OR = 0.66, 95% CI (0.39-1.11), P = 0.12] [OR = 0.85, 95% CI (0.52-1.38), P = 0.50]} compared to placebo. Conclusion This meta-analysis preliminarily suggests that upadacitinib is effective and safe for usage in the treatment of moderate-to-severe AD. Additionally, upadacitinib can instantly relieve itchiness and effectively reduce symptoms and signs, with its 30-mg dose being more effective than the 15-mg dose.